Radio and Nuclear Pharmacy Education & Practice Needs Exploration in India - Kumar, Patel Jyoti Pravin; Kumar, Bhatt Sandip; Kumar, Prakash (Indian Journal of Pharmacy Practice)
RESPECTED SIR, Greetings, we write this letter as our perception on edu- cation of radio and nuclear pharmacy after completion of our project at Nuclear Medicine Department, Civil hospital, Ahmadabad, Gujarat.